Self-service smart pipe capabilities offering based on electronic warrant - Mingxue LI; Yilin LIN; Zhenwei HE (Dianxin kexue)
The limitation of traditional smart pipe capabilities offering was focused,a new self-service network capabilities offering architecture based on the electronic warrant was proposed,including the main service flow,the key technical points and the test result of the current network.